Hemoglobin Levels and Nutrients Intake on Young Soccer Athletes in Yogyakarta (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2019)
The purpose of this study was to know the relationship of nutrients intake and hemoglobin levels in young soccer athletes. This research was an analytical descriptive research with cross-sectional approach. The subjects were 30 athletes of U-13 and U-14 who are active member of SSB Real Madrid UNY. Subjects were measured hemoglobin level using Easy Touch tool. Intake of nutrients were obtained using Semi Quantitative Food Frequency (SQFFQ) form. Data were analyzed using statistical software. Data were processed using chi-square test and pearson correlation. Hemoglobin level in young soccer athletes of SSB Real Madrid was 14.29 Â± 2.16 kg/m2 (normal). Energy intake was poor as many as 15 people (50%), good intake as many as 15 people (50%). Protein intake was good as many as 4 people (13%), poor intake as many as 26 people (87%). Fat intake was poor as many as 18 people (60%), good intake as many as 12 people (40%). Iron intake of 11 people (36.7%) were in poor category, 19 people (63.3%) were normal category. Vitamin C intake as much as 6 people (20%) had poor category, and 24 people (80%) had normal category. There was no significant relationship of energy, protein, fat and iron intake with hemoglobin status (p>0.05). However, there was a significant relationship of carbohydrates and vitamin C intake with hemoglobin levels in athletes (p<0.05). There is no relationship of energy, protein, fat and iron intake with hemoglobin levels. But, there is a relationship of carbohydrates and vitamin C intake with hemoglobin levels of young soccer athletes.